Pencegahan Penyebaran Covid-19 Melalui Edukasi Terapi Imun bagi Tenaga Kependidikan Di Lingkungan Fakultas Ekonomi UNESA - Bahtiar, Moh. Danang; Susanti, Susanti; Susilowibowo, Joni; Widayati, Irin; Tantri Hardini, Han (Universitas Nusantara PGRI Kediri, 2022)
This Community Service activity aims to overcome the spread of Covid-19 within the Faculty of Economics, State University of Surabaya through education for education staff to always apply health protocols through the 5M and MIO movements and increase immunity through consumption of nutritious food during WFO (Work From Office) so that it is expected to be able to increase immunity and will not be easily infected with Covid-19. The results of this PKM activity can be seen from the emergence of habits in implementing the 5M and MIO movements and always consuming multivitamins and intake of nutritious food to increase immunity so that currently there are no records of positive cases of COVID-19 patients among Faculty of Economics Unesa education staff.